Dynamics and Control of a Multi-Rotor Aircraft - Kava, Sean Anthony (Curtin University, 2016)
Despite the fact that aerodynamic loads (forces and moments) induced by airflow relative to a quadrotor vertical take-off and landing aircraft consist of both deterministic and stochastic components, all existing works on controlling the aircraft either ignore these loads or treat them as deterministic. This simplification deteriorates the control performance in a practical implementation. This thesis presents a constructive design of controllers for a quadrotor aircraft to track a reference path in three-dimensional space under both deterministic and stochastic aerodynamic loads.